The proposed model no fault liability scheme for motor vehicle accident claims in Malaysia / Norila Abu Hassan, Noraziah Abdul Jabar and Norha Abu Hanifah - Abu Hassan, Norila; Abdul Jabar, Noraziah; Abu Hanifah, Norha (Research Management Institute (RMI), 2011)
Faultless or at fault, every year the number of those injured rises despite many attempts made by the authorities to curb the toll of motor vehicle accidents. As the consequence of the economic growth in Malaysia and the production of the national car, many can own vehicles thus contributing to the rise in the usage of the major roads in Malaysia. The population increase in Malaysia has led to an increase in vehicle ownership reflective of the growing affluence of the people due to the country's economic progress and prosperity. With the increase in the number of cars, road accidents too are on the rise especially during the months of Malaysian festivals and public holidays where there is an exodus of the urban population to their rural homes. Despite the various attempts made by the Police (OPS SIKAP IX-XXII) from December 2001 to February 2011, the number of accidents has swung upwards from 13442 to 17288 (Perakaan Kemalangan Jalan Raya Musim Perayaan Ops Sikap 1-23 2001-2011). Most of the fatalities involved motorcyclists and their pillion riders, motorists and lately public transport (express buses) users…